The Influence of Artificial Intelligence Adoption and Workforce Digital Readiness on Organizational Growth - Bautista, Rowinner G.; Del Prado, Monica Ivy A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The rapid integration of Artificial Intelligence (AI) technologies has transformed organizational strategies, efficiency, and competitiveness. However, successful adoption depends not only on technological capability but also on workforce digital readiness, which determines how effectively employees adapt to new systems. This study proposes to examine the influence of AI adoption and workforce digital readiness on organizational growth, with a focus on productivity, innovation, and competitive advantage. Using a mixed-methods design, quantitative data will be collected from surveys of organizational leaders and employees across industries, complemented by qualitative interviews to capture deeper insights into challenges and best practices. Despite the growing adoption of AI in the Philippines, limited empirical studies have examined the mediating role of workforce readiness in linking AI adoption to organizational growth, particularly within developing-economy contexts. The findings are expected to provide empirical evidence and policy guidance on how AI and digital readiness interact to shape organizational growth, offering implications for national workforce development strategies, leadership practices, and training programs. This proposal highlights the importance of aligning technological investments with human capital development to maximize organizational outcomes in the digital era.